Optical Coherence Tomography in Mild Cognitive Impairment: A Systematic Review and Meta-Analysis - Mejia-Vergara, Alvaro J.; Restrepo-Jimenez, Paula; Pelak, Victoria S. (Frontiers in Neurology, 2020)
Purpose: The use of optical coherence tomography (OCT) of the retina to detect inner retinal degeneration is being investigated as a potential biomarker for mild cognitive impairment (MCI) and Alzheimer's disease (AD), and an overwhelming body of evidence indicates that discovery of disease-modifying treatments for AD should be aimed at the pre-dementia clinical stage of AD, i.e., MCI. We aimed to perform a systematic review and meta-analysis on retinal OCT in MCI. Methods: We performed a systematic review of the English literature in three databases (PubMed, Embase, and Latindex) for studies that measured retinal thickness using OCT in people with MCI and healthy controls, age 50 or older, between 1 January 2000 and 31 July 2019. Only cohort and case-control studies were reviewed, and independent extraction of quality data and established objective data was performed. We calculated the effect size for studies in the review that met the following criteria: (1) a statistically significant difference between MCI subjects and normal controls for several OCT variables, (2) use of spectral domain OCT, and (3) use of APOSTEL recommendations for OCT reporting. Weighted Hedges' g statistic was used to calculate the pooled effect size for four variables: ganglion cell layer-inner plexiform layer (GCL-IPL) complex thickness in micrometers (μm), circumpapillary retinal nerve fiber layer (pRNFL) thickness in μm, macular thickness in μm, and macular volume in μm3. For variables with high heterogeneity, a multivariate meta-regression was performed. We followed the PRISMA guidelines for systematic reviews. Results: Fifteen articles met the inclusion criteria. A total of 58.9% of MCI patients had statistically significant thinning of the pRNFL compared with normal subjects, while 61.6% of all MCI patients who had macular volume measured had a statistically significant reduction in volume compared with controls, and 50.0% of the macular GCL-IPL complexes measured demonstrated significant thinning in MCI compared with normal controls. Meta-analysis demonstrated a large effect size for decreased macular thickness in MCI subjects compared with normal controls, but there was a substantial heterogeneity for macular thickness results. The other variables did not demonstrate a significant difference and also had substantial heterogeneity. Meta-regression analysis did not reveal an explanation for the heterogeneity. Conclusions: A better understanding of the cause of retina degeneration and longitudinal, standardized studies are needed to determine if optical coherence tomography can be used as a biomarker for mild cognitive impairment due to Alzheimer's disease.